Management of Strengthening Human Resources at Darullughah Wadda'wah International Islamic University, Bangil, Pasuruan - Zainal Abidin (STAI Terpadu Yogyakarta, 2024)
This study examines the management of strengthening human resources at Darullughah Wadda'wah International Islamic University, Bangil, Pasuruan. The topic of study in Islamic educational institutions, especially those based on Islamic boarding schools, as the focus of this research, is of particular interest to researchers. The interest of several researchers in this field of study can be seen from several researches that have been published in scientific journals. This research uses a qualitative approach with a case study design. The study concludes that the management of strengthening human resources at the Darullughah Wadda'wah International Islamic University, Bangil, Pasuruan is carried out through three things, firstly recruiting lecturers and staff professionally, secondly, support for further studies and increasing other capacities and thirdly strengthening scientific publications.